Reframing Reading: Visual Approaches to Comprehension Skills - Putri Lola Sari; Pretia Sari; Darmawan Budiyanto (Media Akademika Publisher, 2026)
This study aimed to investigate the effect of using short video media on students’ reading comprehension among the tenth-grade students of SMA Negeri 10 Palembang. The research employed a quasi-experimental design involving an experimental group and a control group. The data were collected through pre-tests and post-tests administered to both groups, and the results were analyzed using SPSS version 25. The normality and homogeneity tests confirmed that the data met the requirements for parametric testing. The paired sample t-test showed a significant improvement in the reading comprehension scores of students in the experimental group after being taught using short videos. Furthermore, the independent sample t-test revealed a significant difference in post-test scores between the experimental and control groups, with a p-value of 0.033 (p < 0.05). These findings indicate that the use of short video media is effective in enhancing students’ reading comprehension. The study suggests that integrating short videos into English language teaching can increase student engagement, motivation, and overall comprehension skills. Therefore, the short video strategy is recommended as a practical and innovative approach to improve students’ reading abilities in EFL classrooms.